PERTANGGUNGJAWABAN HUKUM BAGI WAJIB PAJAK BERDASARKAN UNDANG-UNDANG NOMOR 7 TAHUN 2021 - Vania Sulistiano; Tanudjaja Tanudjaja (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Tax is a very important and vital aspect in every country. It is important to pay attention to the tax sector to help support the state revenue budget, especially for developing countries. In this case, taxes have an important role as a large source of state revenue, which will later be allocated for state development. This is because it will later be used to fulfill the welfare and prosperity of the people. This writing aims to discuss the responsibility of taxpayers for violations in the field of taxation. Tax payments, whether by an entity or personally, in this case are coercive, so that people are expected to be able to pay taxes in an orderly manner. The problems that arise are generally caused by imbalances between existing tax regulations in Indonesia, both technically and practically as applied. Basically, this problem can be caused by weaknesses in regulations and legal implementation in the tax sector, lack of public understanding and socialization regarding taxes, and low public awareness and awareness of the importance of paying taxes.